2008
DOI: 10.1038/ncponc1201
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel chemotherapy remains the standard of care in castration-resistant prostate cancer

Abstract: This Practice point commentary discusses the findings of a randomized, multicenter, report published by Berthold et al, in which the results of the pivotal TAX 327 study are updated. The original TAX 327 study, published in 2004, randomly allocated men with castration-resistant prostate cancer to one of three chemotherapy regimens: docetaxel 75 mg/m2 administered every 3 weeks, docetaxel 30 mg/m2 administered weekly for 5 of every 6 weeks, or mitoxantrone 12 mg/m2 every 3 weeks. All patients received prednison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…Importantly, it has been reported that some ARVs may elude this effect of microtubule inhibitors, as they may lack the microtubule-binding domain present in full-length AR (24,25) . Historically, docetaxel and cabazitaxel have been used to treat advanced stage PCas (26,27) after hormonal therapies have lost their activity. However, very recent data suggest that early addition of docetaxel with gonadal suppression may significantly increase patient survival compared to later use of the same chemotherapy (28) .…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, it has been reported that some ARVs may elude this effect of microtubule inhibitors, as they may lack the microtubule-binding domain present in full-length AR (24,25) . Historically, docetaxel and cabazitaxel have been used to treat advanced stage PCas (26,27) after hormonal therapies have lost their activity. However, very recent data suggest that early addition of docetaxel with gonadal suppression may significantly increase patient survival compared to later use of the same chemotherapy (28) .…”
Section: Introductionmentioning
confidence: 99%
“…Androgen deprivation therapy (ADT) is initially effective; however, resistance eventually develops in most cases despite aggressive treatment (1). Although medical ADT and orchiectomy are both clinical options, medical ADT with a luteinizing hormone-releasing hormone analog (LHRH-A) is preferred, because orchiectomy is an irreversible procedure involving ethical, psychological, and surgical concerns (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…Although a placebo comparator might seem unwarranted given that docetaxel chemotherapy every 3 weeks is approved by the FDA for metastatic CRPC in symptomatic and asymptomatic patients, both of these trials enrolled only asymptomatic men, and controversy exists regarding the optimal timing of chemotherapeutic intervention in metastatic prostate cancer. 47 …”
Section: Active Immunotherapy For Prostate Cancermentioning
confidence: 99%